The article: The difference of imams is a mercy and its impact on treating sectarian fanaticism - Al-Omari, Samira (Jordan Journal of Islamic Studies, 2023)
This study highlights the fact that there is mercy in the differences of scholars in matters of jurisprudence through the study of the difference of scholars is mercy. It explained the legalization of the study, in addition to that the sayings of scholars in their concept and evidence that they relied on to reach the most correct of their words. The study concluded that the validity of the view says that the difference of the imams are mercy, although his weakness is true only on the meaning, it has a true face in the behavior of scientists and their words according to the controls explained by scientists in the science of difference.